Method for producing high-pressure hydrogen component made of martensitic stainless steel
A manufacturing method for high-pressure hydrogen parts using martensitic stainless steel with a specific composition and heat treatment process addresses the challenges of high nickel content materials, achieving high strength and corrosion resistance at reduced costs and complexity.
Patent Information
- Application Number
- JP2023164123
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing high-pressure hydrogen components face challenges with high nickel content materials like SUH660, which are expensive and require complex heat treatments for high strength, as well as austenitic stainless steels that are costly and difficult to adjust for strength and corrosion resistance.
A manufacturing method for high-pressure hydrogen parts using martensitic stainless steel with a specific chemical composition (C: 0.01-0.05%, Si: 0.70% or less, Mn: 1.10% or less, P: 0.040% or less, S: 0.030% or less, Ni: 4.00-5.70%, Cr: 17.00-20.50%) that undergoes quenching and tempering heat treatments to achieve high tensile strength and corrosion resistance without the need for excessive nickel or complex heat treatments.
The method achieves high tensile strength (900 MPa or more) and 0.2% yield strength (800 MPa or more) while reducing material costs and simplifying the heat treatment process, maintaining excellent properties in both room temperature and high-pressure hydrogen environments.
Smart Images

Figure 2025054904000001 
Figure 2025054904000002 
Figure 2025054904000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for manufacturing a high-pressure hydrogen component made of martensitic stainless steel. [Background technology]
[0002] Stainless steel materials with austenitic structures (austenitic stainless steels) such as SUS316, SUS316L, and SUS305 are generally used for parts that come into contact with high-pressure hydrogen gas in fuel cell vehicles and hydrogen stations (hereinafter referred to as "high-pressure hydrogen parts") These steels have the advantage of being easy to design equipment for, as they show little or no loss in strength in high-pressure hydrogen environments. Furthermore, because they have excellent corrosion resistance, parts made of these steels do not need to be painted, and regular inspections are easy when the parts are in use.
[0003] However, these austenitic stainless steels contain a large amount of Ni, which not only makes them expensive, but also reduces their 0.2% yield strength after solution treatment, resulting in thick-walled, large, and heavy high-pressure hydrogen components such as pipe joints and valves. To solve this problem, cold working is sometimes performed after solution treatment. However, to ensure the desired strength, it is necessary to impart strain corresponding to the desired strength value. However, because the strain distribution inside the component after cold working is complex, it is not easy to freely adjust the strain value through cold working and ensure the desired strength.
[0004] On the other hand, general-purpose martensitic stainless steels such as SUS420J2 and SUS410 do not contain large amounts of Ni, making them less expensive than austenitic stainless steels. Furthermore, their tempered hardness can be adjusted by optimizing heat treatment conditions, making it easier to adjust their strength. However, general-purpose martensitic stainless steels have inferior corrosion resistance compared to austenitic stainless steels, making them difficult to use with their exposed surfaces in high-pressure hydrogen components where relatively high corrosion resistance is required. Additionally, general-purpose martensitic stainless steels have poor toughness at low temperatures, making them difficult to use in high-pressure hydrogen components exposed to low temperatures, such as during hydrogen filling.
[0005] Patent Document 1 proposes the use of martensitic low-alloy steel with relatively small amounts of Ni and Mo for high-pressure hydrogen components. However, the low-alloy steel proposed therein still needs to be improved in terms of corrosion resistance and other aspects, and is not necessarily optimal for use in high-pressure hydrogen components.
[0006] To solve the above problems, a new martensitic stainless steel for high-pressure hydrogen applications has been developed that has improved corrosion resistance and toughness compared to conventional general-purpose martensitic stainless steels, and a patent application has been filed (PCT / JP2023 / 009928).
[0007] The martensitic stainless steel for high-pressure hydrogen components in this prior patent application contains approximately 5% Ni, but the Ni content is lower than that of conventional austenitic stainless steel, allowing for cost reduction. In addition, unlike austenitic stainless steel, the strength can be adjusted by heat treatment, and the properties, corrosion resistance, and low-temperature toughness in a high-pressure hydrogen environment can be ensured at levels that do not pose any problems when used as high-pressure hydrogen components.
[0008] Furthermore, with conventional austenitic stainless steel for high-pressure hydrogen, it is possible to achieve a tensile strength of 700 MPa or more and a 0.2% yield strength of 500 MPa or more, which are strength levels that could not be achieved without cold working to improve strength, and this is characterized by the fact that a fairly high strength can be obtained.
[0009] However, because products such as automobiles that use fuel cells are very expensive, there is a strong demand for cost reductions in the materials used by reducing their weight, etc. Furthermore, for high-pressure hydrogen parts used in gas flow path seals, valve bodies, and other parts that require particularly high strength, there has been a strong demand for the development of technology that can increase the strength even more than the steel proposed in the above application in order to achieve weight reductions.
[0010] Conventionally, SUH660 has been used for high-pressure hydrogen components that require such high strength. This steel can easily achieve high strength through precipitation hardening heat treatment. However, this steel requires the addition of a very large amount of Ni (24-27%), and also contains 1-1.5% Mo and approximately 1.9% Ti, which poses challenges in terms of resource conservation. In addition, the precipitation hardening treatment required to achieve higher strength requires complex multiple heat treatments, which makes the steel very expensive. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 2018-188716 Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made in view of the above background, and aims to provide a manufacturing method that can further improve the tensile strength characteristics of the martensitic stainless steel for high-pressure hydrogen parts described in the prior patent application, and can manufacture high-pressure hydrogen parts made of martensitic stainless steel that can be used in parts requiring high strength, even by using a lower content of elements such as Ni, Mo, Ti, etc. instead of SUH660, and adopting a relatively simple heat treatment. [Means for solving the problem]
[0013] One aspect of the present invention is, in mass %, C: 0.01 to 0.05%, Si: 0.70% or less, Mn: 1.10% or less, P: 0.040% or less, S: 0.030% or less, Ni: 4.00~5.70% Cr: 17.00~20.50%, including Optional elements include Ca: 0.0005 to 0.0030%; As an optional element, B: 0.0005 to 0.0050% is included, The following formula 1 is satisfied: Formula 1:3.0>Ni-0.8Cr+11.36>0, (Note that the element symbols in Formula 1 represent the content (%) of each element.) A method for manufacturing a high-pressure hydrogen component made of martensitic stainless steel having a chemical composition with the balance being Fe and unavoidable impurities, comprising: A part made of a steel material having the above chemical composition is subjected to a quenching heat treatment in which the part is held at a temperature of 860°C to 1020°C and then rapidly cooled, Thereafter, the part is subjected to a tempering heat treatment in which it is held at a temperature of 540°C to 650°C and then air-cooled, in a method for manufacturing a high-pressure hydrogen part made of martensitic stainless steel. [Effects of the Invention]
[0014] According to the manufacturing method for high-pressure hydrogen parts made of the martensitic stainless steel for high-pressure hydrogen parts, by adopting the above-mentioned specific and relatively simple heat treatment on the premise that the stainless steel has the above-mentioned specific chemical composition, it is possible to save resources compared to conventional SUH660 and austenitic stainless steel, and it is also possible to make it possible to easily obtain a martensitic stainless steel having, for example, a tensile strength of 900 MPa or more and a 0.2% yield strength of 800 MPa or more at room temperature in air, and having excellent strength properties even in high-pressure hydrogen. DETAILED DESCRIPTION OF THE INVENTION
[0015] First, the reasons for limiting the chemical composition of the high-pressure hydrogen parts made of the above martensitic stainless steel (hereinafter referred to as "the stainless steel of the present invention") will be explained.
[0016] C: 0.01 to 0.05%, Carbon (C) combines with Cr during tempering heat treatment and precipitates as carbides, reducing the concentration of Cr dissolved in the steel and degrading corrosion resistance. It also reduces the mobile dislocation density in fresh martensite, so a low C concentration is desirable. Furthermore, C increases the hardness of the martensite structure after quenching, making it prone to thermal cracking in the as-quenched state. Avoiding thermal cracking complicates the handling of steel during casting, hot rolling, and hot forging, resulting in increased costs. Therefore, a low C concentration is desirable. Therefore, the C content is limited to 0.05% or less. From the viewpoint of corrosion resistance, a C content of 0.04% or less is preferable.
[0017] On the other hand, if the C concentration is too low and the chemical composition is on the austenite-stable side (martensite-rich side), the steel will contain many crystals with low mobile dislocation density, and after rolling or heat treatment, the steel will be prone to bending due to room temperature creep deformation caused by its own weight, which increases the effort required for straightening and makes it difficult to produce the steel. Therefore, the lower limit of the C content is set at 0.01%.
[0018] Si: 0.70% or less, Silicon (Si) is an essential component for reduction refining in the production of stainless steel. However, because Si is a ferrite-stabilizing element, excessive addition of Si results in the formation of large amounts of ferrite crystals in the metal structure, which are highly susceptible to hydrogen embrittlement. Therefore, the upper limit is set at 0.70%. Preferably, the Si content is 0.60% or less. While there is no specific lower limit for the Si content, it is usually set at 0.10% or more because contamination from the slag components used during refining is unavoidable.
[0019] Mn: 1.10% or less, Mn (manganese) is an essential element for refining stainless steel together with Si. Its inclusion is unavoidable when scrap is used for refining, and in this case, it is typically contained at 0.30% or more. However, excessive addition of Mn can easily form MnS, which reduces corrosion resistance, so the upper limit of the Mn content is set at 1.10%. The Mn content is preferably 1.00% or less, and more preferably 0.80% or less.
[0020] P: 0.040% or less, P (phosphorus) is an element that is inevitably mixed in during the refining process of stainless steel, which uses scrap collected from the market as raw material. Excessive P content makes it more likely to crack during solidification, so the upper limit of the P content is set to 0.040%. Preferably, the upper limit of the P content is set to 0.035%.
[0021] S: 0.030% or less, S (sulfur) combines with Mn in the steel to form MnS, which deteriorates corrosion resistance and hot workability, so the upper limit is set to 0.030%. Furthermore, S segregates at the grain boundaries between austenite and ferrite during hot working, impairing hot workability, so the upper limit is preferably set to 0.010%. More preferably, it is set to 0.005% or less. While there is no particular lower limit for the S content, it is usually set to 0.0005% or more because this is a low-C steel type and it is difficult to extend the reduction refining time.
[0022] Ni: 4.00~5.70% Ni (nickel) is a powerful austenite-stabilizing element, highly effective in suppressing the formation of ferrite crystals, and an important element in improving corrosion resistance. To achieve these effects, Ni should be contained in an amount of 4.00% or more. Preferably, Ni should be contained in an amount of 4.60% or more. However, Ni is an expensive element, and adding a large amount of it lowers the Mf point below room temperature, resulting in the formation of a large amount of retained austenite, which reduces yield strength and corrosion resistance due to microsegregation of the elements. Furthermore, retained austenite can sometimes form strain-induced martensite during plastic deformation at low temperatures, which is detrimental to maintaining strength in a high-pressure hydrogen environment. Therefore, the upper limit of the Ni content is set to 5.70%. Preferably, the upper limit of the Ni content is set to 5.10%.
[0023] Cr: 17.00~20.50%, Cr (chromium) is an important element that contributes to the corrosion resistance of stainless steel. To obtain corrosion resistance comparable to that of Type 439 (UNS S43035) stainless steel, the lower limit is set to 17.00%. The lower limit of the Cr content is preferably set to 17.50%. On the other hand, a high Cr concentration increases the amount of ferrite, making it difficult to maintain tensile strength in a low-temperature, high-pressure hydrogen environment. Therefore, the upper limit is set to 20.50%. The upper limit of the Cr content is preferably set to 19.50%.
[0024] Optional elements include Ca: 0.0005 to 0.0030%; The addition of small amounts of Ca (calcium) bonds with S in steel to form CaS, thereby reducing the amount of S dissolved in the steel and improving its hot workability. In the case of the stainless steel of the present invention, the addition of Ca reduces the amount of dissolved S, thereby suppressing S segregation to grain boundaries, particularly during hot working at temperatures above 1150°C, and significantly improves the ductility of the steel during hot working. However, Ca is not necessarily a necessary element when hot working at temperatures below 1150°C.
[0025] To obtain the effect of improving hot workability by adding Ca, it is preferable to add 0.0005% or more. On the other hand, excessive addition of Ca increases the amount of oxide-based inclusions in the steel, so the upper limit is preferably set to 0.0030%. When adding Ca, it is preferable to add it simultaneously with B, which also has the effect of suppressing S segregation to grain boundaries.
[0026] As optional elements, B: 0.0005 to 0.0050%; The addition of a small amount of B (boron) has the effect of suppressing S segregation to grain boundaries and improving hot workability. In the case of the stainless steel of the present invention, the addition of B reduces the amount of solute S, thereby suppressing S segregation to grain boundaries, particularly during hot working at temperatures above 1150°C, and significantly improves the ductility of the steel during hot working. However, B is not necessarily an essential element when hot working at temperatures below 1150°C.
[0027] As mentioned above, the addition of B is not essential, but if the effect of improving hot workability is to be obtained by its addition, it is necessary to add at least 0.0005% or more of B, and preferably 0.0020% or more. On the other hand, excessive addition of B can increase unintended inclusions such as borides, so the upper limit should be set to 0.0050%, and preferably 0.0040%. When adding B, it is preferable to add it simultaneously with Ca, which also has the effect of suppressing S segregation to grain boundaries.
[0028] Formula 1:3.0>Ni-0.8Cr+11.36>0, (Note that the element symbols in Formula 1 represent the content (%) of each element.)
[0029] Formula 1 defines the range in which an appropriate metal structure can be obtained by restricting the amount of ferrite structure while making the martensite structure the main phase in the quenched and tempered heat treatment state.
[0030] Although Equation 1 is simple, by setting the lower limit to a component range exceeding 0, it is possible to control the metal structure so that the amount of ferrite structure does not become excessive (for example, 40% or less in area ratio), and to make the mechanical properties (tensile strength, 0.2% yield strength) in a low-temperature, 90 MPa, high-pressure hydrogen environment at -45°C almost equivalent to those in air.
[0031] In iron with a BCC crystal structure, when plastic deformation occurs in a hydrogen-containing environment, such as in a high-pressure hydrogen environment, the vacancy concentration within the crystal increases as dislocations move during plastic deformation. This is widely known as the hydrogen-assisted vacancy theory. Given that the vacancy concentration in steel increases due to plastic deformation in a hydrogen environment, it is inferred that as the increase in vacancies due to hydrogen during plastic deformation facilitates the diffusion of iron atoms, this promotes crystal slip deformation, leading to the generation of microcracks before cross-slope slip occurs, resulting in localized stress concentrations and a decrease in the ductility of steel in a hydrogen environment.
[0032] Therefore, in order to increase elongation in iron with a BCC crystal structure in hydrogen-containing conditions, such as high-pressure hydrogen environments, and maintain tensile strength equivalent to that in air, it is necessary to ensure that as many slip planes as possible are active so that many dislocations do not move along the same slip plane. From this perspective, tempered martensite crystals have more random crystal orientation per volume than ferrite crystals, and many amorphous grain boundaries, etc., making them advantageous for reducing the decrease in elongation in hydrogen. Therefore, it is preferable to keep the ferrite content as low as possible. However, in the present stainless steel, from the perspective of corrosion resistance, a Cr content of at least 17.00% tends to increase the ferrite content. Therefore, we actively introduced Equation 1 to limit the ferrite content by setting the lower limit to greater than 0.
[0033] It is also possible to narrowly control the amount of Cr and Ni added without using Equation 1 to achieve the appropriate amount of ferrite, but this narrows the compositional range, making manufacturing difficult. Furthermore, in the refining of stainless steel, Ni, an expensive additive element, is a component that cannot be removed. Furthermore, during the reduction refining phase, where the amount of Cr, a relatively inexpensive additive element, is determined by controlling the composition of the steel, there is no way to lower its concentration other than by diluting it. Therefore, using Equation 1 is useful from the perspective of steel refining, where it is necessary to control the Cr content so that it does not become too high while monitoring the actual value of expensive Ni.
[0034] Furthermore, since retained γ (austenite) may induce strain-induced martensite during use and cause a decrease in ductility, it is preferable to suppress it as much as possible. This suppression of retained γ can be achieved by setting upper limits for various elements including Ni and setting the upper limit of the above formula 1 to less than 3.0, thereby obtaining a structure containing ferrite (for example, an area fraction of 5% or more).
[0035] Next, it is preferable that high-pressure hydrogen components made of the stainless steel of the present invention have a tensile strength of 900 MPa or more and a 0.2% yield strength of 800 MPa or more in air at room temperature.
[0036] High-pressure hydrogen components made of the stainless steel of the present invention are subjected to pressure tests in which a gas pressure exceeding the design pressure is applied, and high yield strength is desirable to prevent plastic deformation of the components that would impair their original functions before use. However, since even higher yield strength is desirable to achieve weight reduction, it is preferable to ensure a tensile strength of 900 MPa or more and a 0.2% yield strength of 800 MPa or more. On the other hand, although there is no need to specify upper limits for the tensile strength and 0.2% yield strength, if the tensile strength is too high, the machinability of the components will decrease, so to avoid deterioration of machinability, it is preferable to limit them to 1000 MPa or less, and in this case, the 0.2% yield strength will also be limited to a value lower than that value.
[0037] Next, when manufacturing high-pressure hydrogen components made of the stainless steel of the present invention, a component made of a steel material having the above-mentioned chemical composition is subjected to a quenching heat treatment in which it is held at a temperature of 860°C to 1020°C and then rapidly cooled, and then the component is subjected to a tempering heat treatment in which it is held at a temperature of 540°C to 650°C and then air-cooled.
[0038] The decrease in strength due to the decrease in ductility in a high-pressure hydrogen environment is particularly problematic at low temperatures. It is well known that in stainless steels such as SUS304, which are primarily composed of FCC crystals, strain-induced martensite is the cause of the decrease in ductility and strength. On the other hand, in the present stainless steels, which are primarily composed of BCC crystals and have almost no retained austenite, or even if it does exist, it is negligible at less than 5%. The decrease in ductility in hydrogen due to the decrease in lattice vibration with decreasing temperature is thought to be due to the fact that dislocation motion that crosses slip planes becomes more difficult to occur, resulting in the concentration of dislocation movement, i.e., atomic diffusion, on specific slip planes.
[0039] To use BCC steels in a high-pressure hydrogen environment, it is important to maintain the required strength while reducing the dislocation density before plastic deformation and preventing the concentration of dislocation movement (diffusion of substitutional atoms) on specific slip planes. Furthermore, it is desirable to actively utilize the crystal interfaces where the atomic arrangement that satisfies these requirements is in an amorphous state. From this perspective, it is considered desirable to use a martensite structure as the main phase, which has the advantage of having more grain boundaries and other interfaces per volume compared to a ferrite structure.
[0040] The amount of ferrite mixed into the structure reduces strength in a high-pressure hydrogen environment. Therefore, for steel materials with the above-mentioned composition ranges and defined by the above-mentioned formula 1, the quenching temperature should be set to 860°C to 1020°C. If the quenching temperature is less than 860°C, the steel is susceptible to changes in the austenite / ferrite phase ratio during cooling, which may result in a non-uniform hardness distribution across the cross section of the part. If the quenching temperature exceeds 1020°C, the ferrite content may become excessive, which may result in a decrease in strength in a high-pressure hydrogen environment. Therefore, the quenching temperature should preferably be set to 890 to 950°C.
[0041] Furthermore, water cooling, oil cooling, etc. can be used as a method for rapidly cooling the part after it has been held in the quenching holding temperature range.
[0042] Next, after the above-mentioned quenching heat treatment, the part is subjected to a tempering heat treatment in which the part is held at a temperature of 540°C to 650°C and then air-cooled. By carrying out this tempering heat treatment, high tensile strength and excellent low-temperature toughness can be obtained in air and in a high-pressure hydrogen environment.
[0043] If the holding temperature in the tempering heat treatment is less than 540°C, phase separation may occur, which may reduce low-temperature brittleness, and if it exceeds 650°C, the effect of improving yield strength due to precipitates may be difficult to obtain. Therefore, the holding temperature in the tempering heat treatment after the quenching heat treatment is preferably 560 to 640°C. In addition, air cooling is used in this case because experimental results have shown that air cooling sufficiently improves strength. Here, air cooling means so-called natural cooling in the atmosphere (including cooling with the aid of air blowing), and is cooling at a cooling rate of approximately 0.2 to 3.0°C / second between 600°C and 400°C.
[0044] Next, high-pressure hydrogen components made of the present stainless steel preferably have an absorbed energy of 100 J or more in a V-notch Charpy impact test under low-temperature conditions at -60°C. High-pressure hydrogen components are exposed to low temperatures not only due to environmental temperatures but also due to pre-cooling and temperature drops caused by the expansion of hydrogen gas when large amounts of high-pressure hydrogen gas are consumed in a short period of time. Therefore, low low-temperature toughness of steel is undesirable from a safety perspective. The standard KHKS0220 (2020) for ultra-high-pressure gas equipment requires that high-pressure hydrogen equipment satisfy the toughness requirement of a Charpy impact test using a V-notch with a thickness of 10 mm and a V-notch depth of 2 mm at the minimum design metal temperature. Each test specimen must have an absorbed energy of 21 J or more, and the average absorbed energy of the three specimens must be 27 J or more. While this requirement is of course to be met, an absorbed energy of 100 J or more has been made a mandatory characteristic to ensure a level equivalent to that of conventional austenitic stainless steels. This will further improve the reliability of high-pressure hydrogen components.
[0045] Next, it is preferable that high-pressure hydrogen components made of the present stainless steel do not lose their mechanical properties in a high-pressure hydrogen environment. That is, if the 0.2% yield strength and tensile strength in a high-pressure hydrogen environment are lower than those in air, the strength of the steel in air cannot be utilized in high-pressure hydrogen, making the mechanical design and quality assurance of the components extremely difficult. It is also generally known that the effect of high-pressure hydrogen on the mechanical properties of steel is particularly pronounced at low temperatures. Therefore, it is preferable that the tensile strength and 0.2% yield strength do not lose significantly in a high-pressure hydrogen environment at low temperatures compared to those in air.
[0046] Specifically, when comparing the tensile strength A1 and 0.2% yield strength A2 in a low-temperature, high-pressure hydrogen environment (-45°C, 90 MPa pressure) with the tensile strength B1 and 0.2% yield strength B2 in a low-temperature, high-pressure nitrogen environment (-45°C, 0.1 MPa pressure), it is preferable that both A1 / B1 and A2 / B2 be 0.95 or greater. By satisfying this ratio, the stainless steel of the present invention is significantly less affected by high-pressure hydrogen and can maintain mechanical properties in a high-pressure hydrogen environment that are nearly equivalent to those in atmospheric pressure. Furthermore, by limiting the chemical composition and using a heat treatment method optimized to achieve the high strength, extremely high tensile strength and yield strength can be achieved in both air and high-pressure hydrogen environments, as shown in the examples described below.
[0047] The properties in a low-temperature, high-pressure hydrogen environment were represented by the properties in a low-temperature, high-pressure hydrogen environment at a temperature of -45°C and a pressure of 90 MPa. Tensile tests were also conducted under the same conditions using test pieces of the same shape as above in a low-temperature nitrogen environment at a temperature of -45°C and a pressure of 0.1 MPa, and this was used for comparison. The conditions in this low-temperature nitrogen environment simulate low-temperature air, eliminating the effects of ice formation due to moisture in the air.
[0048] Next, high-pressure hydrogen components made of the stainless steel of the present application preferably have a metallographic structure consisting essentially of martensite and ferrite, and the martensite preferably contains a mixture of tempered martensite and fresh martensite. Here, fresh martensite refers to as-quenched martensite, which is a martensite structure newly formed by tempering heat treatment. Furthermore, a metallographic structure consisting essentially of martensite and ferrite refers to a phase in which the area ratio of the combined martensite (including tempered martensite and fresh martensite) and ferrite phases is 95% or more.
[0049] In order to ensure the low-temperature toughness of stainless steel, it is thought that increasing the mobile dislocation density is necessary. To achieve this, it is effective to minimize the amount of C added in the chemical composition and use a martensite structure with an extremely low C content. Furthermore, it is preferable to use a composition that produces a small amount of fresh martensite even after tempering.
[0050] Furthermore, since retained austenite may induce deformation-induced martensite during use, it is preferable to minimize its formation. In martensitic stainless steels containing 17% or more Cr, such as the stainless steel of the present invention, it is difficult to suppress retained austenite in a metallographic structure with a high martensite phase ratio. Therefore, in order to suppress retained austenite, it is preferable to have a structure containing ferrite. In other words, it is most preferable that the stainless steel of the present invention contains an extremely low concentration of C, 17% or more Cr, and has a metallographic structure of "tempered martensite + ferrite + fresh martensite."
[0051] The area ratio of ferrite is preferably in the range of 5% to 40%. If the area ratio of ferrite is less than 5%, there is a problem that the 0.2% yield strength decreases, while if it exceeds 40%, there is a problem that it is difficult to maintain strength in a low-temperature, high-pressure hydrogen environment.
[0052] Next, high-pressure hydrogen parts made of the present stainless steel can be applied to parts for a variety of applications that come into contact with high-pressure hydrogen. Specific examples of such parts include pipe joints, valves, pressure accumulators, safety valves, receptacles, filling nozzles, and boosters. In particular, the present stainless steel can be applied without problem to high-pressure hydrogen parts used in gas flow path seals, valve bodies, and other parts that require particularly high strength. [Example]
[0053] An example of a method for manufacturing high-pressure hydrogen components made of the present stainless steel will be described.
[0054] (Experimental Example 1) In this example, as shown in Tables 1 and 2, two types of steel were prepared, samples were produced by changing the heat treatment conditions, and various evaluations were performed.
[0055] [Table 1]
[0056] [Table 2]
[0057] <Preparation of steel material (sample)> After being melted, each steel material was hot forged into a round bar of φ25 by elongation processing, and each round bar was subjected to heat treatment under the heat treatment conditions (heat treatments 1 to 3) shown in Table 2 to prepare samples for evaluation.
[0058] Heat treatment 1 is the condition for quenching heat treatment, and heat treatment 2 is the condition for tempering heat treatment after quenching heat treatment. In all of Examples 1 to 10, samples were prepared by carrying out quenching heat treatment (heat treatment 1) and tempering heat treatment (heat treatment 2) in which the cooling condition after heating was air cooling. In Reference Examples 1 and 2, samples were prepared by not only quenching heat treatment (heat treatment 1) and tempering heat treatment (heat treatment 2), but also by further carrying out a subsequent re-tempering heat treatment (heat treatment 3). In both Heat Treatment 2 and Heat Treatment 3 in Reference Examples 1 and 2, the cooling condition after heating was water cooling. Reference Examples 1 and 2 are examples shown as Example 1 and Example 11 in the above-mentioned prior application. The steel material used in Example 1 and Reference Example 1 of the present application is the same as that used in Example 1 of the prior application, with only the heat treatment conditions being different. Similarly, the steel material used in Examples 2 to 10 of the present application and Reference Example 2 is the same as that used in Example 11 of the prior application, with only the heat treatment conditions being different. Therefore, by comparing the evaluation results of both, it is possible to compare the differences in effects due to differences in heat treatment conditions.
[0059] <Microstructure observation> A specimen was cut from each round bar of steel so that a cross section perpendicular to the longitudinal direction was exposed as the observation surface. The observation surface was polished and then etched with Murakami's reagent. The image obtained by observing the observation surface with an optical microscope was analyzed to confirm the ferrite area ratio. A ferrite area ratio between 5% and 40% was evaluated as passing, and anything outside this range was evaluated as failing. The obtained area ratio values are shown in Table 3.
[0060] <Tensile test in air> The tensile strength and 0.2% yield strength at room temperature in air were determined by taking JIS 14A test pieces with a parallel section diameter of 8 mm from each steel material in accordance with JIS Z2241 (2011, Tensile Testing Method for Metallic Materials) so that the length of the steel material was the same as the length of the test piece, and conducting tensile tests using these. For tensile strength at room temperature in air, a value of 900 MPa or greater was evaluated as passing, and a value less than 900 MPa was evaluated as failing. For 0.2% yield strength at room temperature in air, a value of 800 MPa or greater was evaluated as passing, and a value less than 800 MPa was evaluated as failing. The values obtained are listed in Table 3.
[0061] <Tensile tests under low-temperature, high-pressure hydrogen and low-temperature nitrogen environments> For the tensile tests in a low-temperature, high-pressure hydrogen environment, tensile test specimens with a parallel section diameter of 6 mm and a parallel section length of 30 mm were taken from each steel material, with the length of the steel material aligned with the length of the test specimen. The tensile tests were then conducted at a slow stroke speed of 0.0015 mm / s in an apparatus capable of realizing a low-temperature, high-pressure hydrogen environment at a temperature of -45°C and a pressure of 90 MPa. This type of tensile test at a slow strain rate is called SSRT (Slow Strain Rate Testing).
[0062] The tensile test in the low-temperature nitrogen environment was carried out in the same manner as in the low-temperature, high-pressure hydrogen environment, except that the atmospheric conditions were changed to a low-temperature nitrogen environment at a temperature of -45°C and a pressure of 0.1 MPa.
[0063] In comparing the tensile strength A1 and 0.2% yield strength A2 in a low-temperature, high-pressure hydrogen environment with the tensile strength B1 and 0.2% yield strength B2 in a low-temperature, nitrogen environment, a specimen was evaluated as passing (○) if both A1 / B1 and A2 / B2 were 0.95 or higher. A1 / B1 is called the relative tensile strength (RTS), and A2 / B2 is called the relative yield strength (RYS).
[0064] <Low temperature Charpy test> For the low-temperature Charpy test, a 10mm thick, 2mm deep V-notch test piece was taken from each steel material, as specified in JIS Z2242 (2018, Charpy impact test method for metallic materials), and this was used to carry out the test in an air atmosphere at -60°C. A test with an absorbed energy of 100J or more was evaluated as passing (○).
[0065] <Pitting potential measurement> The pitting potential was measured using a sample taken from each steel material so that the surface parallel to the longitudinal direction of the steel material was the test surface, using a method in accordance with JIS G0577 (2014, Method for measuring pitting potential of stainless steel). Specifically, the pitting potential was measured from the anodic polarization curve in a 1 mol / L sodium chloride aqueous solution (30°C) at a current density of 0.1 mA / cm. 2 The potential (V'c100) corresponding to this value was measured and evaluated as the pitting potential. A saturated KCl silver-silver chloride electrode at 30°C was used as the reference electrode, and the potential was converted to a saturated KCl electrode standard (vs. SCE) by subtracting 45 mV from the reference electrode, and the measured value was used as the pitting potential.
[0066] The standard was 185mV vs SCE, which is the measurement value for Type 439 stainless steel, which is recognized as having sufficient corrosion resistance in general environments, and anything above that was rated as passing (〇).
[0067] The evaluation results are shown in Table 3.
[0068] [Table 3]
[0069] As shown in Tables 1 to 3, although the heat treatment conditions for Examples 1 to 10 were slightly different, all of them underwent a first heat treatment, a quenching heat treatment in which the part was held at a temperature of 860°C to 1020°C followed by rapid cooling, and a second heat treatment, a tempering heat treatment in which the part was held at a temperature of 540°C to 650°C followed by air cooling. All of the samples had appropriate chemical compositions, satisfied Equation 1, and met all of the evaluation criteria, demonstrating that they possessed excellent properties that met all of the evaluation criteria, making them suitable for use in high-pressure hydrogen components and overcoming technical challenges in reducing their cost. Furthermore, all of the samples exhibited excellent mechanical properties, such as a tensile strength of 900 MPa or more and a 0.2% proof stress of 800 MPa or more in room-temperature air, while maintaining excellent tensile properties, low-temperature toughness, and corrosion resistance in a low-temperature, high-pressure hydrogen environment.
[0070] Furthermore, as shown in Table 3, Reference Examples 1 and 2 also maintained excellent properties in terms of tensile properties, low-temperature toughness, and corrosion resistance in a low-temperature, high-pressure hydrogen environment, while also showing significantly improved strength properties in air at room temperature compared to conventional examples. In contrast, Examples 1 to 10 of the present application described above maintained performance such as tensile properties, low-temperature impact value, and corrosion resistance in a high-pressure hydrogen environment without deterioration, and further improved tensile strength and yield strength, and all examples were able to secure a tensile strength of 900 MPa or more and a 0.2% yield strength of 800 MPa or more. This shows that the heat treatment method of subjecting a part made of steel having the specific chemical composition to a quenching heat treatment in which the part is held at a temperature of 860°C to 1020°C and then rapidly cooled, and then subjecting the part to a tempering heat treatment in which the part is held at a temperature of 540°C to 650°C and then air-cooled, is a very effective heat treatment method for improving strength when manufacturing high-pressure hydrogen components made of martensitic stainless steel having the chemical composition.
Claims
1. In mass percent, C: 0.01-0.05%, Si: 0.70% or less, Mn: 1.10% or less, P: 0.040% or less, S: 0.030% or less, Ni: 4.00-5.70%, Cr: 17.00 to 20.50%; Optional elements include Ca: 0.0005 to 0.0030%; As an optional element, B: 0.0005 to 0.0050% is included, The following formula 1 is satisfied: Formula 1: 3.0>Ni-0.8Cr+11.36>0, (Note that the element symbols in formula 1 represent the content (%) of each element.) A method for producing a high-pressure hydrogen component made of martensitic stainless steel having a chemical composition with the balance being Fe and unavoidable impurities, comprising: A part made of a steel material having the above-mentioned chemical composition is subjected to a quenching heat treatment in which the part is held at a temperature of 860°C to 1020°C and then rapidly cooled; The method for manufacturing a high-pressure hydrogen component made of martensitic stainless steel then includes subjecting the component to a tempering heat treatment in which the component is held at a temperature of 540°C to 650°C and then air-cooled.
2. The high-pressure hydrogen part has an absorbed energy of 100 J or more obtained by a V-notch Charpy test with a thickness of 10 mm and a V-notch depth of 2 mm as described in JIS Z2242 (2018, Charpy impact test method for metallic materials) under a low temperature condition of -60 ° C. In a tensile test in which a tensile test piece having a parallel portion diameter of φ6 mm and a parallel portion length of 30 mm is pulled at a stroke speed of 0.0015 mm / sec, in a comparison of tensile strength A1 and 0.2% yield strength A2 in a low-temperature, high-pressure hydrogen environment at a temperature of -45°C and a pressure of 90 MPa, and tensile strength B1 and 0.2% yield strength B2 in a low-temperature nitrogen environment at a temperature of -45°C and a pressure of 0.1 MPa, both A1 / B1 and A2 / B2 are 0.95 or more, The method for producing a high-pressure hydrogen component made of martensitic stainless steel according to claim 1, wherein the martensitic stainless steel has a pitting potential of 185 mV (vs SCE) or more.
3. 3. The method for producing a high-pressure hydrogen part made of martensitic stainless steel according to claim 1, wherein the high-pressure hydrogen part has a tensile strength of 900 MPa or more and a 0.2% yield strength of 800 MPa or more at room temperature in air.
4. 3. The method for manufacturing a high-pressure hydrogen component made of martensitic stainless steel according to claim 1 or 2, wherein the high-pressure hydrogen component has a metal structure substantially consisting of martensite and ferrite, and the martensite is a mixture of tempered martensite and fresh martensite, and the area ratio of the ferrite is in the range of 5% to 40%.
Citation Information
Patent Citations
Low alloy steel for hydrogen accumulator, and hydrogen accumulator
JP2018188716A